Manajemen Fisioterapi pada Kasus Inkontinensia Urin pada Lansia: Studi Kasus - Ningsih, Fitriya; Wijianto, Wijianto; Muflihah, Nurul (VISA: Journal of Vision and Ideas, 2025)
Urinary incontinence is one of the common disorders experienced by the elderly, especially women, and has a significant impact on the quality of life, both physically and psychologically. This case report aims to evaluate the effectiveness of physiotherapy interventions against urinary incontinence in 75-year-old female patients. Treatment methods include an initial examination using the Numeric Rating Scale (NRS) pain scale, assessment of muscle strength with Manual Muscle Testing (MMT), and symptom severity through the Overactive Bladder Symptom Score (OABSS). Physiotherapy interventions were carried out as many as four sessions consisting of infrared therapy, abdominal exercise, and Kegel exercise, accompanied by education and home exercise programs. The results showed a decrease in pain when urinating from a score of 5 to 0, an increase in abdominal muscle strength from a score of 3 to 4, and pelvic floor muscle from a score of 1 to 2. The OABSS score also decreased from 11 to 5, indicating a significant improvement in urinary incontinence symptoms. In conclusion, physiotherapy has a positive impact on reducing complaints and improving muscle function in the elderly with urinary incontinence. This report contributes to supporting the use of physiotherapy as an effective non-invasive approach in the management of sleep disorders in the elderly population.